2016
DOI: 10.1007/s40521-016-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for the Phenotyping and Monitoring of Asthma in Children

Abstract: Opinion statementAn important issue in relation to the utility and reliability of biomarkers for asthma monitoring is how asthma is defined and characterized. What kind of asthma, or at what stage of the disease is a particular biomarker supposed to add information? Often, the purpose, or usefulness of a biomarker is not made clear. Diagnosis, severity evaluation, and monitoring are all different clinical uses for a biomarker, and confusion may arise when a biomarker is suitable for one of these but not anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 96 publications
(97 reference statements)
0
23
0
1
Order By: Relevance
“…There is an imminent need to discover new biomarkers that can discriminate and classify different asthmatic phenotypes, predict the clinical behavior and therapeutic response as well as aid in the identification of new therapeutic targets. 8,9 Those markers need to be less invasive and more technically convenient in comparison to the currently available ones. 10 Despite that necessity, only a few markers were shown to have potential roles in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is an imminent need to discover new biomarkers that can discriminate and classify different asthmatic phenotypes, predict the clinical behavior and therapeutic response as well as aid in the identification of new therapeutic targets. 8,9 Those markers need to be less invasive and more technically convenient in comparison to the currently available ones. 10 Despite that necessity, only a few markers were shown to have potential roles in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…29 For instance, baseline POSTN levels were high in children and hence might mask any changes due to its local release within the airways leading to inconsistent findings in children. 9 Therefore, we explored publicly available datasets to identify possible confounders affecting POSTN gene expression and hence may limit the interpretation of its level in the clinical settings. Our analysis showed that POSTN gene mRNA expression was upregulated in the asthmatic, smoker COPD and IPF bronchial epithelium when compared to matching healthy controls (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Поиску маркеров БА в образцах крови в настоящее время уделяется большое внимание [4]. В числе потенциальных диагностических маркеров рассматривается периостин -протеин, экспрессируемый преимущественно эпителиальными клетками, а также фибробластами и гладкомышечными клетками бронхов [5,6].…”
Section: обоснованиеunclassified